Pro and Contra of the Parliamentary Threshold among Electoral Management Bodies (EMBs) and Political Parties: Seeking a Relevant Model for Indonesia’s Legislative Election - Al-Hamdi, Ridho; Sakir, Sakir; Lailam, Tanto (Journal of Governance and Public Policy, 2022)
This paper is going to examine the pro and contra among the Electoral Management Bodies’ (EMBs) commissioners and political parties’ functionaries in responding to the parliamentary threshold issue. Methodologically, this paper is based on qualitative research by utilizing a multiple case approach. It is supported by employing Qualitative Data Analysis Software (Q-DAS), namely NVivo 12Plus to analyse the data written in the transcript of the Focus Group Discussion (FGD) with the EMBs’ commissioners and politicians in six provinces and nine cities/counties. The finding demonstrates that the all actors agree to adopt the parliamentary threshold in the national legislative election. Afterward, the mind map contains distinctive issues among EMBs and politicians. Thus, the parliamentary threshold is still required to strengthen the consolidation of Indonesian democracy. Such a threshold is also an essential standard to encourage well institutionalized parties and to modernize them. Thus, four percent of the parliamentary threshold is an ideal model. Subsequently, the increase of the parliamentary threshold percentage is no needed anymore. In addition to that, it is not applied in the regional legislative election.